Musical Iconography in the Romanesque of the Province of Soria - Rodríguez Pérez, Nerea (Eikón / Imago, 2013)
This study begins with the iconographic analysis of the portal of Santo Domingo in Soria and spreads to the itinerary of Romanesque remains throughout this province, with the elaboration of routes in search of the remaining musical sources. The result of this study is the compilation of all the Romanesque musical iconography in the province od Soria, its possible means of influence and the catalogation of the sources, with a catalogue of musical scenes located in the Romanesque remains in this province and a series of outdoor musical sources found in 20 of the 210 examined locations.